Asymmetric Synthesis of Enantiopure Pyrrolidines by C(sp3)−H Amination of Hydrocarbons. (27th August 2021) - Lazib, Yanis; Retailleau, Pascal; Saget, Tanguy; Darses, Benjamin; Dauban, Philippe
Abstract: The asymmetric synthesis of enantiopure pyrrolidines is reported via a streamlined strategy relying on two sequential C−H functionalizations of simple hydrocarbons. The first step is a regio‐ and stereoselective catalytic nitrene C−H insertion. Then, a subsequent diastereoselective cyclization involving a 1, 5‐hydrogen atom transfer (HAT) from a N‐centered radical leads to the formation of pyrrolidines that can then be converted to their free NH‐derivatives. Abstract : Simple hydrocarbons such as alkanes are shown to be useful building blocks for the asymmetric synthesis of heterocycles. They are converted in only two steps to pyrrolidines by application of stereoselective C(sp 3 )−H amination reactions. Symmetrical and non‐symmetrical enantiopure 2, 5‐disubstituted pyrrolidines are isolated in good yields.